The Influence of Investment Decisions, Funding Decisions, Risk of Strategy, To Efficeincy, Finance Performance, Value of Firm, Good Corporate Governance As Moderating Variable In The Mining Company Coal Sub Sector Go Public In Indonesia Stock Exchange - Matiin, Nuuridha; Ratnawati, Tri; Riyadi, Slamet (Archives of Business Research, 2018)
The problems of the mining company is the financial performance of various issuers in the mine sector is not encouraging I-quarter 2012. Average-performance emitters of mining records profit below expectations. The decline in profit that, triggered by the production down and did not reach its target production. Some companies are old as TINS and ANTM. Conditions were worsened by the weather that keeps rain and drought if erratic. The purpose of this study is to determine The Influence of Investment Decisions, Funding Decisions, Risk of Strategy, To Efficeincy, Finance Performance, Value of Firm, Good Corporate Governance (GCG) as The Moderate Variable In The Mining Company Coal Sub Sector Go Public In Indonesia Stock Exchange. The population used in this study is the whole mining company coal sector sub go public in Indonesia stock exchange (idx), which obtained the data from the Indonesian Capital Market Directory (ICMD). Sample from a population of 18 companies. This research uses of data analysis in SEM (Structure Equational Modeling) using the Partial Least Square 2.0. The results obtained show that Investment decisions don’t effect significantly to efficiency, Investment decisions effect significantly to financial performance, Investment decision effect significantly to value of firm, Funding decisions effect significantly to efficiency, Funding decisions effect significantly to financial performance, Funding decisions effect significantly to value of firm, Risk of strategy effect significantly to efficiency, Risk of strategy effect significantly to financial performance, Risk of strategy don’t effect significantly to value of firm, Efficient effect significantly to financial performance, Efficient effect significantly to the value of firm, GCG as moderating variable effect significantly to value of firm, GCG as moderating variable effect significantly to financial performance and Financial performance effect significantly to value of firm.